2019
DOI: 10.3389/fendo.2019.00570
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Mitochondrial Dynamics and Metabolism in Obesity, Diabetes, and Cancer

Abstract: Metabolism describes the life-sustaining chemical reactions in organisms that provide both energy and building blocks for cellular survival and proliferation. Dysregulated metabolism leads to many life-threatening diseases including obesity, diabetes, and cancer. Mitochondria, subcellular organelles, contain the central energy-producing metabolic pathway, the tricarboxylic acid (TCA) cycle. Also, mitochondria exist in a dynamic network orchestrated by extracellular nutrient levels and intracellular energy need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
105
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(111 citation statements)
references
References 126 publications
6
105
0
Order By: Relevance
“…Mdivi-1 (a widely accepted DRP1 inhibitor) induced cancer cell death and decreased tumour size in xenograft models. 4,19 Mdivi-1 increased OCR in non-cancer cells like mouse neuroblastoma 58 but deceased OCR in human ductus arteriosus smooth muscle cells. 59 Similar to these findings, studies showed that mdivi-1 increased OCR in some cancer cells 60,61 but decreased OCR in other cancer cells.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Mdivi-1 (a widely accepted DRP1 inhibitor) induced cancer cell death and decreased tumour size in xenograft models. 4,19 Mdivi-1 increased OCR in non-cancer cells like mouse neuroblastoma 58 but deceased OCR in human ductus arteriosus smooth muscle cells. 59 Similar to these findings, studies showed that mdivi-1 increased OCR in some cancer cells 60,61 but decreased OCR in other cancer cells.…”
Section: Discussionmentioning
confidence: 97%
“…15,16 Mitochondrial fusion and fission contribute to these morphologic changes and are often dysregulated under pathological conditions, including cancers. 18,19,25,28,51 Most studies of cancer-related mitochondrial dynamics focus on their function in apoptosis, [52][53][54] and elevated mitochondrial fission has been linked to impaired oxygen consumption in cancer cells. 18,[55][56][57] However, it is not clear whether mitochondrial dynamics regulate metabolic alterations in cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial dynamics play a pivotal role in diverse cellular processes, such as adipocyte differentiation, lipid homeostasis, and oxidative metabolism. Adipose tissue mitochondrial dysfunction contributes significantly to the pathogenesis of obesity-associated metabolic diseases (Cedikova et al, 2016;Chouchani & Kajimura, 2019;Dai & Jiang, 2019;Lee et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity and other metabolic diseases are associated with adipose tissue dysfunction and attenuated beigeing and browning efficiencies (Dai & Jiang, 2019). However, the molecular mechanisms are not completely understood.…”
Section: Discussionmentioning
confidence: 99%